Handbook on appropiate technology for forestry operations in developing countries - Part 2 - Kantola, Mikko. Harstela, Pertti (Finlandia : FTP, 1991)
Trata de Handbook on appropiate technology for forestry operations in developing countries.
1. Cost Factors 2. The planning Frammework
incluye índice
Col. Agro
Keywords: 1. TRANSPORT BY ANIMALS ON ROADS 2. CABLE YARDING